Developing substrate-based small molecule fluorescent probes for super-resolution fluorescent imaging of various membrane transporters. Issue 3 (13th November 2019) - Wu, Qiang; Cai, Mingjun; Gao, Jing; Zhao, Tan; Xu, Haijiao; Yan, Qiuyan; Jing, Yingying; Shi, Yan; Kang, Chuanqing; Liu, Yi; Liang, Feng; Chen, Junling; et al.
Abstract : Glucose-based probes and tyrosine-based probes as novel small molecule fluorescent probes are synthesized for super-resolution fluorescent imaging of glucose transporters and tyrosine transporters on cellular membranes. Abstract : Super-resolution imaging technology has been a powerful tool for revealing fine biological structures and functions. Its high-quality imaging always needs highly accurate labeling. Here, by exploiting the high specificity and affinity of natural substrates to transporters, we developed one set of substrate-based small molecule fluorescent probes for labeling membrane transporters. A glucose-based probe (Glu-probe) and tyrosine-based probe (Tyr-probe) were synthesized as two examples. Confocal imaging showed that the Glu-probe could label glucose transporters on live cells by being stuck into the binding site. Compared with antibody-probe labeling, the labeling advantages of the Glu-probe were revealed. High specificity of the Glu-probe or Tyr-probe was examined by a colocalization experiment and glucose replacement or amino acid (AA) blocking. The synthetic probes were also tested on imaging HeLa cells to confirm their wide labeling application. Additionally, we found that membrane transporters were mostly in the clustered state on cellular membranes, changing their assembly pattern to regulate the transport effectiveness. These results suggest that the substrate-based probes can serve as valuable tools for investigating the spatial information of membrane transporters.